Robust Versus Optimal Rules in Monetary Policy : A Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
We provide a framework for analyzing the choice between optimal and robust monetary policy rules in the presence of paradigm uncertainty. We first discuss the conditions on uncertainty that render a robust rule preferable to an optimal rule. Second, we show how the degree of risk aversion of the policymaker increases the region in which the robust rule is preferred.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Central Bank; Depository Institutions; Micro Finance Institutions; WP